Impact of 2016 WHO diagnosis of early and overt primary myelofibrosis on presentation and outcome of 232 patients treated with ruxolitinib. Issue 4 (7th June 2019) - Palandri, Francesca; Palumbo, Giuseppe A.; Abruzzese, Elisabetta; Iurlo, Alessandra; Polverelli, Nicola; Elli, Elena; Bonifacio, Massimiliano; Bergamaschi, Micaela; Martino, Bruno; Tiribelli, Mario; Benevolo, Giulia; Tieghi, Alessia; et al.
Abstract: The 2016 WHO criteria identified early primary myelofibrosis (PMF) as an individual entity with milder clinical features and better outcome compared with overt PMF. Here, we compared early and overt PMF patients treated with ruxolitinib in terms of baseline clinical/laboratory characteristics, response, and toxicity to treatment. We observed that early‐PMF patients achieve better and more stable spleen and symptoms responses, with significantly lower rates of hematological toxicities. No differences in overall and leukemia‐free survival were detected between the two cohorts. The application of 2016 WHO criteria is crucial to identify those PMF patients who deserve a stricter monitoring during treatment.